Accounting Records Using the Android Application to Evaluate Changes in Earnings - Fitriana, Avincennia Vindy; Wijaya, Indra; Oktapriana, Chita (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2020)
The purpose of this research is to test the difference in the logging of profit conducted by Micro, Small, and Medium Enterprises (MSME) with the recording in accordance with accounting standards and to test the feasibility of Akuntansi UKM application in the implementation in MSME business. The respondents of this research are the MSME in Bekasi City under the Dinas Koperasi dan UKM. There were 40 respondents in this study. This research is a case study research and uses quantitative descriptive methods. Data analysis Using test paired t-test and application feasibility test using PIECES. The results of this research are there is a difference between the average profit that has been recorded by the respondents with the profit recorded in accordance with the financial accounting standards, and the Akuntansi UKM application has fulfilled the eligibility criteria so that it can be applied in business actors, especially MSME.